An Analysis of Impact of Teamwork on Employee Performance and Organization Growth (International Journal of Innovative Research in Engineering & Management, 2021)
Teamwork may be defined as working together  collaboratively with other members of the organization to  achieve the organization's approved goals. Teamwork is very  important in an organization in order to minimize the residual  load and, on the whole, carry out all of the organization's tasks  efficiently. It may help the organization in its recent rushes to  support on the lookout and make the most of the relative  variety of assets in the organization. A team may be described  as a collection of people who work together to accomplish the  same objectives and goals in order to offer high-quality  services. Teamwork has the potential to provide team  members with a better degree of emotional stability, self confidence, and the ability to plan and make good decisions  with others. It also aids in the creation of a healthy work  environment by facilitating the development of viable  agendas, innovative activities, positive tactics, and values. On  the other side, a lack of collaboration ideas and methods may  lead to job failure, disappointment, low morale, and poor  productivity, all of which endanger the organization's  existence. This investigation focuses on how teamwork may  influence the association's overall condition and how it can  have a beneficial impact on both the association and its  representatives.
Keywords: Assets; Cooperation; Collaboration; Profitability; Teamwork